2017
DOI: 10.1007/s10585-017-9857-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of the neural niche in brain metastasis

Abstract: Cancers with neurologic metastasis are a burdensome affliction. As primary cancer care improves, the incidence of metastatic cancer increases as a result of prolonged survival time. Because of this, advances in the understanding of the mechanisms of metastasis are important for the development of continuing management strategies. Knowing how metastatic tumor cells engage, survive, and proliferate in the central nervous system (CNS) is an important first step in developing treatment paradigms. The neural niche … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…2A, B). It was recently reported that a complex reciprocal communication between metastatic tumor cells and other brain stoma cells primed the successful outgrowth of overt brain metastases, which was dependent on the release of some factors, including secreted soluble proteins or small vesicles (such as exosomes) (20,21). To establish the existence of the exosomes in HBMECconditioned medium, the medium was collected from the coculture system in which the HBMECs were labeled by Syto fluorescence in advance.…”
Section: Resultsmentioning
confidence: 99%
“…2A, B). It was recently reported that a complex reciprocal communication between metastatic tumor cells and other brain stoma cells primed the successful outgrowth of overt brain metastases, which was dependent on the release of some factors, including secreted soluble proteins or small vesicles (such as exosomes) (20,21). To establish the existence of the exosomes in HBMECconditioned medium, the medium was collected from the coculture system in which the HBMECs were labeled by Syto fluorescence in advance.…”
Section: Resultsmentioning
confidence: 99%
“…Metastasis is a process rather than a simple endpoint, wherein the arrest of the cancer cells occurs at vascular branch points, cancer cells have to remain close to microvessels, and perivascular growth by early angiogenesis is predominant in lung cancer and by vessel co-option in melanoma [77]. In comparison, breast cancer cells that reach the brain exhibit a GABAergic phenotype similar to neuronal cells, They can use GABA as an energy metabolite and increase cell survival [79, 80].…”
Section: The Tumor Microenvironment In Brain Metastasesmentioning
confidence: 99%
“…These factors activate astrocytes to produce growth factors (IL-6, IL-1B, and tumor necrosis factor), resulting in a perpetuation of cancer cell growth in the neural niche ( 18 ). Activation of VEGF, Notch pathways and secretion of BMP-2 (a growth factor that differentiates neuronal stem cells into astrocytes) sustain neoangiogenesis in BMs and tumor–astrocyte interactions ( 19 ).…”
Section: Biology and Pathophysiology Of Bmsmentioning
confidence: 99%